ChemInform Abstract: NaSH in the Construction of Thiophene Ring Fused with N‐Heterocycles: A Rapid and Inexpensive Synthesis of Novel Small Molecules as Potential Inducers of Apoptosis. Issue 9 (March 2015) - Kolli, Sunder Kumar; Nakhi, Ali; Medishetti, Raghavender; Yellanki, Swapna; Kulkarni, Pushkar; Ramesh Raju, R.; Pal, Manojit
Abstract The first examples of the use of NaSH to construct a thiophene ring fused with N‐heterocycles via a SnAr‐type reaction—cyclization strategies are given.